Peningkatan Literasi Siswa Melalui Kampus Mengajar - Santa Miralda Lumbantobing (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2022)
In an effort to overcome the low literacy skills of students in Indonesia, the Ministry of Education and Culture held a Campus  Teaching  program, which is to send selected students to elementary / junior high schools with the aim of helping four things, namely literacy, numeracy, technology adaptation and administration. One of the targets of the Teaching Campus 3 program is SMPN 1 OKU in South Sumatra, which is carried out for approximately three months starting from March to June 2022. It aims to improve students' literacy and numeracy skills in taking the PISA test. The methods applied are varied and consist of three stages, namely the preparation, implementation, and evaluation stages. The evaluation of this activity is a sharing session and test implementation. The training participants are students of class VIII-1 and VIII-2 by taking the Pre-Test and Post Test for Literacy-Numeracy through the AKM Class application to evaluate the final abilities related to student literacy-numeracy. In the implementation of the post-test, students were very enthusiastic to take the test. Overall, students who participated in the literacy-numeracy training experienced a significant increase in their abilities.